Political Sophistication and Populist Party Support : The Case of PTB-PVDA and VB in the 2019 Belgian Elections - Gallina, Marta; Baudewyns, Pierre; Lefevere, Jonas (Politics of the Low Countries, 2025)
In this article, we investigate the moderating role of political sophistication on the vote for populist parties in Belgium. Building on the literature about the diverse determinants of populist party support, we investigate whether issue considerations and populism-related motivations play a bigger role in the electoral calculus of politically sophisticated voters.Using data from the 2019 general elections in Belgium, we focus on the cases of Vlaams Belang (VB) and Parti du Travail de Belgique- Partij van de Arbeid (PTB-PVDA). We find evidence suggesting that political sophistication enhances the impact of populism-related motivations on populist party support, although the effects are contingent on the party. Moreover, we show that, for issue considerations, the moderation effect only comes into play for VB voters: the impact of anti-immigrant considerations is greater at increasing levels of political sophistication.